Development of Drawing Art Through The Expanded Technique - mubaroh, mufi; Tamtomo, Sigit; Pramono, Koko Hari (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
Painting, as a fine art discipline, typically involves the conversion of human experiences, both internal and external, into a two-dimensional material, such as paper or canvas. Paintings are distinguished by their emotion, necessitating effective conveyance. The production of quality paintings necessitates a foundation of knowledge and proficiency in techniques. Supporting components encompass a fundamental comprehension of visual elements and principles, as well as a diligent observation of worldwide occurrences to remain informed about contemporary issues and advancements in painting. The fundamental skills in painting encompass applying color using brush strokes, followed by the process of generating repetitive lines, known as shading techniques. Shading techniques are fundamental methods in the creation of drawing art. The current period offers boundless opportunities for elaboration and collaboration, encompassing a range of creation processes and the research of mediums, from traditional to expanded forms. The liberty to utilize diverse mediums influences the evolution of painting with shading techniques, transitioning from traditional drawing to expanded drawing, which encompasses art that transcends conventional materials like paper or canvas.